Urban mobility & inequality in public services in Dhaka city: An analysis of accessibility of transportation for people with disabilities (Pwds) - Nahar, Noor-E-Fayzun (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Development Studies, 2019.